PERAN UNION OF EUROPEAN FOOTBALL ASSOCIATION (UEFA) DALAM MENGATASI PERMASALAHAN ANAK-ANAK TERLANTAR DI UGANDA TAHUN 2019 - Randi Daniel Siregar; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes how the efforts of the European football international organization, UEFA, in overcoming the problem of neglected children in Uganda in 2019. Uganda is one of the largest countries that has a population under the age of 18. Therefore, the problem level of neglected children in Uganda is also very high. Many of the cases of neglected children problems in Uganda were caused by domestic violence, and also the conflict in Northern Uganda in 1987. The Ugandan government has also made various efforts to address the problems of neglected children in Uganda, but these efforts have been in vain. in vain because there is no solution that seeks to address the problem of neglected children in Uganda from its roots. This study uses qualitative research methods, with data collection techniques through literature studies sourced from several books, journals, articles, and also websites. This study also uses a pluralism perspective, the level of group behavior analysis, and also uses international organization theory to further strengthen this research. The results of this study indicate that UEFA has made efforts to address the problem of abandoned children in Uganda. In an effort to overcome the problem of abandoned children in Uganda, UEFA carries out its role in accordance with the roles of international organizations according to Clive Archer, namely UEFA as an instrument, forum or facilitator, and also as an independent actor in efforts to overcome the problems of abandoned children in Uganda in 2019. Keywords: Football in Uganda, UEFA, Neglected Children in Uganda, Conflict in Northern Uganda